PRÉSENTATION D’UNE APPROCHE NUMÉRIQUE POUR LA MODÉLISATION DE LA DYNAMIQUE SEDIMENTAIRE: CAS DU LITTORAL DE MOHAMMEDIA (MAROC) - Idrissi, Mohammed; Gouaud, Fabrice; Rey, Vincent; Makaoui, Ahmed; Ettahiri, Omar; Hilmi, Karim; Chagdali, Mohamed; Hourimeche, Ahmed (European Scientific Journal, ESJ, 2015)
We present numerical modelling to study the impact of natural and anthropic process on the sedimentary dynamic. This approach is based on the numerical modelling of wave propagation and of sediment transport in order to predict the shoreline evolution. The results concern the localization of erosion or accretion areas. A long term shoreline evolution can be determined. This multidisciplinary method is applied to the case of the Mohammedia coast (Morocco).